Materiały kultury trzcinieckiej i tarnobrzeskiej kultury łużyckiej ze stanowiska Wierzawice 4, pow. leżajski w świetle analiz archeologicznych/Materials of the Trzciniec culture and Tarnobrzeg Lusatian culture coming from the site Wierzawice 4 in the light of archaeological analyses - Rajpold, Wojciech; Adamik-Proksa, Joanna; Burghardt, Marcin (My University, 2016)
The subject of the present article is to describe the materials of the Trzciniec culture (KT) and the Tarnobrzeg Lusatian culture (TKŁ) coming from the studies conducted by K. Moskwa in 1978 and K. Ormian in 2001 at the site Wierzawice 4. KT materials, coming from this site, are represented by settlement features and sherds of pottery which can be dated to the classical phase of this culture. While TKŁ materials are represented by 23 burial complexes (21 urn cremation burials, single urnless cremation and inhumation burials) dated to I phase and the beginning of II phase of this culture, whereas the younger settlement materials came from III phase
Keywords: Tarnobrzeska kultura łużycka; kultura trzciniecka; wschodnie wpływy; epoka brązu; wczesna epoka żelaza; archeologia funeralna